Rainfall drives rapid shifts in carbon and nutrient source-sink dynamics of an urbanised, mangrove-fringed estuary. (5th February 2021) - Reithmaier, Gloria M.S.; Chen, Xiaogang; Santos, Isaac R.; Drexl, Michael J.; Holloway, Ceylena; Call, Mitchell; Álvarez, Paula Gómez; Euler, Sebastian; Maher, Damien T.
Abstract: Estuaries provide valuable ecosystem services, such as carbon storage and nutrient retention, which may be affected by episodic rainfall events. This study aimed to investigate the short-term effect of episodic rainfall on alkalinity, dissolved carbon and nutrient biogeochemistry in a small, urbanised and mangrove-fringed estuary. High temporal resolution sampling (1.5-h interval) at upper and lower estuary sites, as well as groundwater sampling, were conducted over two weeks to assess estuarine source/sink dynamics of total alkalinity (TAlk), organic alkalinity (OAlk), dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), nitrate, nitrite, ammonium and phosphate. Rapid, short-term changes in estuarine biogeochemistry and mixing were triggered by two episodic rainfall events, which delivered 26 mm over 2 h and 39 mm over 21 h. The estuary was a source for TAlk and DIC exporting 2.2 ± 1.9 and 2.2 ± 1.5 mmol/m 2 catchment/d, respectively, to the coastal ocean during the observation period. On average, OAlk accounted for 8% of TAlk at the upstream and 3% at the downstream site. Unlike pristine mangrove systems, the estuary was a net sink for DOC, equivalent to ~23% of the DIC source. Rainfall increased catchment nutrient inputs into the estuary, which was a source for ammonium, but a sink for nitrate and nitrite (NOx ) throughout the study period. In contrast, phosphate dynamics were less clear. Estuarine biogeochemical transformations affected the exchange with the coastal ocean, driving net TAlk export and by acting as a sink for catchment-derived nutrients. Our high-temporal resolution results suggest that rainfall events rapidly modify estuarine biogeochemistry and mixing, altering the net fluxes of TAlk, dissolved carbon and nutrients to the coastal ocean. Graphical abstract: Image 1 Highlights: Rainfall triggered rapid biogeochemical changes at a subtropical estuary. The estuary removed anthropogenic NOx, attenuating fluxes to the coastal ocean. The estuary was a source of alkalinity and DIC to the coastal ocean. Organic alkalinity accounted for 3–8% of the total alkalinity. A net DOC removal was observed within the estuary.